Protection of Human Rights in the Investigation Process Criminal Offenses in Indonesia - Elisa Pitria Ningsih (PT. Anagata Sembagi Education, 2024)
The criminal investigation process is the initial stage in the criminal justice system that has great potential for human rights violations. This research aims to analyze the implementation of human rights protection in the criminal investigation process in Indonesia, with a focus on identifying obstacles and challenges faced, and providing recommendations for improvement. The research method used is a qualitative approach with normative analysis of various national and international legal instruments governing human rights protection, as well as case studies and in-depth interviews with law enforcement officials and legal experts. The results showed that although Indonesia has a strong legal framework to protect human rights, as stipulated in the 1945 Constitution, Law No. 39/1999 on Human Rights, and the Criminal Procedure Code (KUHAP), there are still various obstacles in its implementation. Cases of torture and inhumane treatment, detention without legal procedures, and limited access to legal aid are still common. The main causes of these problems are lack of oversight, lack of training of law enforcement officials on human rights, and limited resources to provide adequate legal aid.